Self- and co-regulation in european caregiver-child dyads: age-related changes and validity of the IMMA-SF questionnaire - Pauen, Sabina; Mata, Cecil; Fumagalli, Monica; Giannì, Maria L.; Morniroli, Daniela; Książek, Justyna; Marijnissen, Lotte; Southgate, Victoria; Pluta, Agnieszka; Kampis, Dora (European psychologist, 2025)
Children’s capacity to regulate their impulses increases during early years, supported by their caregivers’ co-regulation. The questionnaire IMMA (Impulse-Management in the Caregiver-Child Dyad; Pauen et al., 2019) assesses (1) parental ideas and goals regarding child self-regulation development, (2) child self-regulation strategies, and (3) parental co-regulation strategies. A total of N = 2,478 parents from Denmark, Germany, Italy, and Poland with children aged 1–6 years (M = 36.34, range 12–83 months) filled out the IMMA short-form online. The factor structure reached an adequate model fit in all countries and closely resembled that of the original version, with few interesting exceptions. Cross-sectional analyses revealed that parents’ expectations regarding child self-regulation development, children’s self-regulation-, and parents’ co-regulation strategies changed dynamically throughout early childhood. Based on the findings, we conclude that the IMMA-SF provides a valid instrument to further explore this interplay across development.